PENGUKURAN PERSEPSI DOSEN FAKULTAS TEKNIK TENTANG IMPLEMENTASI REMUNERASI DI UNIVERSITAS PATTIMURA - Alfredo Tutuhatunewa; Ariviana L. Kakerissa; Tradessantia Syatauw (ALE Proceeding, 2021)
This study aims to determine the perception of lecturers of the Faculty of Engineering on the policy of implementing remuneration at the Pattimura University. Perceptions related to remuneration implementation can be measured from several indicators, including grading determination, tariff setting, performance reporting system, reward system, performance appraisal system as well as experience and years of service. The analysis was carried out by clustering using K-mean cluster. The results showed that of the three clusters formed, there were significant differences, with high, medium and low perceptions. The limitations of the study and suggestions for further research are discussed at the end of this paper.